Analisis Minat Generasi Z Untuk Mengisi Survei Online - Austin Abdul Aziz Riano Junior; Waris Marsisno (Politeknik Statistika STIS, 2022)
Rapid technological advances coupled with the COVID-19 pandemic require the adoption of the internet in all non-survey fields. An online survey is a survey that uses an online website-based questionnaire. However online surveys tend to have low response rates. Younger age and behavior affect online survey response rates. Behavior can be researched using Theory of Planned Behavior. Regarding age, Generation Z will be the most involved in online surveys. This study aims to find out the general description of Generation Z's interest in filling out online surveys which are explained based on the Theory of Planned Behavior. The survey respondents in this study were Generation Z (17+). The results were analyzed using binary logistic regression. The results show that Generation Z's interest in filling out online surveys is much lower and the Theory of Planned Behavior can be used to explain Generation Z's interest in filling out online surveys.